The Role of Pathgoal Theory's Leadership Style in Improving Employee Work Motivation: A Literature Study in Various Multidisciplined - Wijaya, Danis Suma; Wening, Nur (Jurnal Ekuisci, 2024)
The work motivation of its employees influences the success of a company. As a determinant of the company's targets, a leader must be able to motivate employees to work optimally. Pathgoal theory is a type of leadership style that focuses on employee motivation. This literature review study aims to determine the influence of path theory leadership style on work motivation. The method used is a systematic literature review obtained with search tools such as Google Scholar and Researchgate. There are four scientific articles analyzed. The theory of leadership style path goals affects employee work motivation. There are four types of leadership styles based on pathgoal theory: directive, supportive, participatory, and achievement-oriented.